The protein interaction of mitochondrial transcription factors A and B2 is associated with 30-day survival in critical COVID-19 - Westhus, Britta; Thon, Patrick; Palmowski, Lars; Rump, Katharina; Koos, Björn; Wiebel, Frederik; Dyck, Birte; Eisenacher, Martin; Sitek, Barbara; Pfaender, Stephanie; Babel, Nina; Anft, Moritz; et al. (Frontiers in Immunology, 2025)
IntroductionRepair of mitochondrial damage seems pivotal for clinical recovery and determining outcome in patients with critical COVID-19. However, reliable biomarkers for non-invasively assessing mitochondrial repair in peripheral blood of critically ill COVID-19 patients are currently lacking. Accordingly, we sought to assess different surrogates of mitochondrial repair in peripheral blood and correlate these measurements with clinical outcome in patients with critical COVID-19.MethodsIn this prospective multicentric cohort study, 88 critically ill COVID-19 patients were enrolled across three German intensive care units. Gene products of mitochondrial quality control (MFN2, PINK, TFAM, TFB2M) and the mtDNA copy number were measured in peripheral blood mononuclear cells. Furthermore, the protein interactions between TFAM and TFB2M were quantified. Patients were stratified regarding 30-day mortality. ResultsTranscript levels of the assessed mRNA markers of mitochondrial quality control were not associated with clinical outcome. In contrast, more than 10.7 protein interactions per cell were associated with a 74% 30-day survival (37 out of 50), while 10.7 or fewer protein interactions per cell were associated with a 32% 30-day survival (12 out of 38; p < 0.001). Furthermore, multivariable Cox regression analysis revealed TFAM-TFB2M protein interaction as an independent predictor for 30-day survival (HR: 3.2; 95% CI: 1.6 to 6.5; p < 0.001). DiscussionOur findings indicate that TFAM-TFB2M protein interactions, identified as a novel biomarker, are strongly and independently associated with 30-day survival in critical COVID-19. Therefore, our data suggest a significant impact of mitochondrial repair and quality control on clinical outcome in critical COVID-19.